2003
DOI: 10.1128/jvi.77.17.9632-9638.2003
|View full text |Cite|
|
Sign up to set email alerts
|

Maedi-Visna Virus and Caprine Arthritis Encephalitis Virus Genomes Encode a Vpr-Like but No Tat Protein

Abstract: A small open reading frame (ORF) in maedi-visna virus (MVV) and caprine arthritis encephalitis virus (CAEV) was initially named "tat" by analogy with a similarly placed ORF in the primate lentiviruses. The encoded " Tat Lentiviruses comprise a genus of complex, nononcogenic retroviruses that infect diverse mammalian hosts, including primates (human immunodeficiency virus [HIV] and simian immunodeficiency virus), carnivores (feline immunodeficiency virus), and ungulates (equine infectious anemia virus, bovine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 27 publications
(14 reference statements)
0
36
0
Order By: Relevance
“…Given that macrophage is the main (and sometimes the only) target cell for lentiviruses, 54 the fact that both primate and nonprimate lentiviruses encode a Vpr-like protein 55 indicates a critical role that this protein plays in lentiviral infection of macrophages. Therefore, the activity of Hsp70 to bind and neutralize Vpr is likely an important innate antilentiviral mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Given that macrophage is the main (and sometimes the only) target cell for lentiviruses, 54 the fact that both primate and nonprimate lentiviruses encode a Vpr-like protein 55 indicates a critical role that this protein plays in lentiviral infection of macrophages. Therefore, the activity of Hsp70 to bind and neutralize Vpr is likely an important innate antilentiviral mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent studies on the initially named Tat protein of Small Ruminant Lentiviruses (SRLV), infecting goats and sheep, showed that this protein has a minimal effect on the transcriptional level from the LTR [181]. In fact, the gene initially designed as the tat gene may encode a Vpr-like protein, suggesting that SRLV differ from the other lentiviruses in their control of expression from the viral LTR [180].…”
Section: Tat Rev and S2: The Accessory Proteins Of Eiavmentioning
confidence: 99%
“…The U3 region contains the promoter and enhancer regions of the virus, and unlike human immunodeficiency virus (HIV), no transactivation response element has been identified in the R region. The Tat protein of MVV has in most studies been shown to activate transcription 2-to 8-fold (compared to 100-fold activation by HIV type 1 [HIV-1] Tat) and has been suggested to be analogous to the Vpr protein in HIV-1 (6,16,56). The LTR has been associated with tissue tropism in a number of retroviruses (11,14,32,35,38,39,49,55).…”
mentioning
confidence: 99%